Application of Law Information and Electronic Transactions in Crime Investigation of Online Gambling - Farris Nur Sanjaya (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Internet in Indonesia has an important influence on the shape of society. All of lifestyle conveniences provided, of course, continue to provide a negative influence on the life of the nation. Crime using the internet is also increasing, one of the crime of online gambling. So that the police in order to conduct an investigation into the crime of online gambling, using the Law of the Republic of Indonesia Number 11 Of 2008 on Information and Electronic Transactions (Act of ITE). With the provision regulating digital evidence and electronical proof in Act of ITE, it would be easier for the police in evidence and law enforcement against the perpetrators of the crime of online gambling.Keywords: Act of ITE, Investigations, Online gambling.